Uterine and placental distribution of selected extracellular matrix (ECM) components in the dog. Issue 5 (May 2018) - Graubner, Felix R; Boos, Alois; Aslan, Selim; Kücükaslan, Ibrahim; Kowalewski, Mariusz P
Abstract : For many years, modifications of the uterine extracellular matrix (ECM) during gestation have not been considered as critical for successful canine ( Canis lupus familiaris ) pregnancy. However, previous reports indicated an effect of free-floating blastocysts on the composition of the uterine ECM. Here, the expression of selected genes involved in structural functions, cell-to-cell communication and inhibition of matrix metalloproteinases were targeted utilizing qPCR and immunohistochemistry. We found that canine free-floating embryos affect gene expression of FN1, ECM1 and TIMP4 . This seems to be associated with modulation of trophoblast invasion, and proliferative and adhesive functions of the uterus. Although not modulated at the beginning of pregnancy, the decrease of structural ECM components (i.e. COL1, -3, -4 and LAMA 2 ) from pre-implantation toward post-implantation at placentation sites appears to be associated with softening of the tissue in preparation for trophoblast invasion. The further decrease of these components at placentation sites at the time of prepartum luteolysis seems to be associated with preparation for the release of fetal membranes. Reflecting a high degree of communication, intercellular cell adhesion molecules are induced following placentation ( Cx26 ) or increase gradually toward prepartum luteolysis ( Cx43 ). The spatio-temporal expression of TIMPs suggests their active involvement in modulating fetal invasiveness, and together with ECM1, they appear to protect deeper endometrial structures from trophoblast invasion. With this, the dog appears to be an interesting model for investigating placental functions in other species, e.g. in humans in which Placenta accreta appears to share several similarities with canine subinvolution of placental sites (SIPS). In summary, the canine uterine ECM is only moderately modified in early pregnancy, but undergoes vigorous reorganization processes in the uterus and placenta following implantation.